Rationale and design of the Anti-Xa Therapy to Lower cardiovascular events in Addition to standard therapy in Subjects with Acute Coronary Syndrome–Thrombolysis in Myocardial Infarction 51 (ATLAS-ACS 2 TIMI 51) trial: A randomized, double-blind, placebo-controlled study to evaluate the efficacy and safety of rivaroxaban in subjects with acute coronary syndrome - Gibson, C. Michael; Mega, Jessica L.; Burton, Paul; Goto, Shinya; Verheugt, Freek; Bode, Christoph; Plotnikov, Alexei; Sun, Xiang; Cook-Bruns, Nancy; Braunwald, Eugene (The American heart journal, 2011)
Although therapy with aspirin or aspirin plus a thienopyridine reduces the incidence of long-term adverse cardiovascular events among patients with acute coronary syndrome (ACS), there remains a significant residual risk of cardiovascular death, recurrent myocardial infarction (MI), and stroke. In a phase 2 trial (ClinicalTrials.gov NCT00402597) in which the addition of the factor Xa inhibitor rivaroxaban was compared with placebo, among ACS patients receiving either aspirin alone or dual-antiplatelet therapy with aspirin and a thienopyridine, the end point of death, MI, or stroke compared with placebo was reduced (87/2331 [3.9%] vs 62/1160 [5.5%]; hazard ratio 0.69, [95% CI 0.50-0.96], P = .027). Two candidate doses of rivaroxaban were selected for further evaluation in a pivotal phase 3. The second ATLAS-ACS 2 TIMI 51 Trial is an international, randomized, double-blind, event-driven (n = 983) phase 3 trial involving more than 15,570 patients hospitalized with ACS (ClinicalTrials.gov NCT00809965). All patients are treated with a background of standard therapy including low-dose aspirin, and patients are stratified by the administration of a thienopyridine (clopidogrel or ticlopidine; stratum 2) or not (stratum 1). Within each stratum, patients are randomly assigned in a 1:1:1 ratio to receive rivaroxaban 2.5 mg twice daily, or rivaroxaban 5 mg twice daily, or placebo twice daily. The primary efficacy end point is the composite of cardiovascular death, MI, or stroke. The primary safety end point is thrombolysis in MI major bleeding not associated with coronary artery bypass graft surgery. The ATLAS-ACS 2 TIMI 51 is testing the hypothesis that anticoagulation with the oral factor Xa inhibitor rivaroxaban reduces cardiovascular death, MI, and stroke among patients with ACS treated with guideline-based therapies for ACS.